$e^{iπ}+1=0.$
$e^{iπ}=-1.$
$e^{-iπ}=-1^{-1}.$
$e^{-iπ}=-1=e^{iπ}.$
$-iπ=iπ.$
$-i=i.$
$1=-1$ .[dividing by -i]
In which line did I make mistake?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The mistake is when you use $e^{i\pi} = e^{-i\pi}$ to conclude $i\pi = -i\pi$ . The exponential function $e^z$ is not a $1-1$ function on the complex plane. One cannot conclude $z_1 = z_2$ simply because $e^{z_1} = e^{z_2}.$ (Indeed, the exponential function is periodic along the imaginary axis - a central fact of complex analysis.)